Water-soluble magnetic nanoparticles as potential agents for magnetic hyperthermia - V. K. Khlebnikov; H. M. Vishwasrao; M. А. Sokolskaya; A. V. Kabanov (Тонкие химические технологии, 2012)
Magnetic nanoparticles (MNPs) obtained by two methods - thermal decomposition of iron(V) pentacarbonyl and polyol synthesis - were characterized with the use of dynamic/electrophoretic light scattering and high resolution transmission electron microscopy. The obtained MNPs were tested as potential agents for magnetic hyperthermia by measuring their ability to cause water dispersion heating in an electromagnetic field.